Concentration and amount of nutrients in Teca seedlings produced in organic substrates - Trazzi, Paulo André; Delarmelina, William Macedo; Caldeira, Marcos Vinicius Winckler (Revista Ecologia e Nutrição Florestal - ENFLO, 2014)
Industrial, urban and agricultural residues can be used as a source of nutrients to contribute to reducing the costs of seedling production. The aim of this study was to determine the concentraton and the amount of nutrients in seedlings of Tectona grandis produced in organic substrate. The seedlings were grown in tubes with volumetric capacity of 280 cm³, filled with two groups of residues and constituting two studies. The first consisted in formulating substrates with biosolids associated with carbonized rice hull or shredded coconut fiber in the proportions 80:20, 60:40, 40:60, 20:80 (v:v), and with 100% BIO forming the basis of nine treatments BIO undergoing treatment compared with the commercial forestry substrate. The second study was characterized by using ratios (v:v:v) for 15, 25 or 35% of cattle manure, poultry litter or quail manure associated with subsoil (60, 50 or 40%, respectively) and 25% commercial forestry substrate forming a set of nine treatments were compared to treatment with commercial forestry substrate. The substrates formed these treatments were subjected to chemical and physical analyzes. To evaluate the nutritionally seedlings, shoots was subjected to chemical analysis. Considering the concentrations and amounts of nutrients, the highest were obtained in the treatment with 80% BIO + 20% CAC, for the treatments with biosolid. For the study of animal manure, the largest amount of nutrients was observed in the treatment with 35% CF. The BIO 60 and 80% associated with CAC or FC promoted greater gains in height, diameter, dry mass of shoots and roots, in the experiment with sewage sludge.